Research and application of G-SRv6 head compressions optimization technology - Weiqiang CHENG; Yisong LIU; Wenying JIANG; Geng ZHANG (Dianxin kexue)
As the key technology of the new generation IP network,SRv6 has gradually become the direction of network evolution in the 5G and cloud networks.The problems how to solve the problems of excessive head overhead,low payload efficiency,and difficult upgrading from the existing network has become the focus of the industry.Based on this technical problem,header compression design principles were proposed firstly,including mechanism compatible with standard SRv6 header encapsulation,inheriting the advantages of standard SRv6 and IPv6,compatible with existing network address plan,achieving an effective balance of compression efficiency and processing performance,and interconnecting with existing networks.Secondly,a G-SID header compression solution was proposed based on common prefix stitching,the key technical capabilities of G-SID container,COC flavor,and SID index were defined,and a network orchestration solution for mixed deployment of compressed and uncompressed networks was proposed.Finally,the progress of the G-SID solution in the industry’s international standards was introduced,and has been verified by the interoperability of multi-vendor equipment,and the pilot deployment on the existing network was planned to promote the rapid deployment of SRv6 on the entire network.